Experimental Investigation in Heat Dissipation Capability of Copper Oxide Nanoparticle Additive Blended Lubricant of Viscosity 15W-40 Operating on A 3.0L Turbocharged Diesel Engine - Devkota, Lochan Kendra; Bhusal, Amit; Khatri, Nirmal; Bhattarai, Prajwal; Giri, Sujeep; Pant, Bhuwesh (International Journal on Engineering Technology and Infrastructure Development, 2025)
This study explores the thermal management capabilities of copper oxide nanoparticle additive blended lubricant in internal combustion (IC) engines, focusing on its potential to enhance heat dissipation compared to conventional lubricant. For this, first of all copper oxide nanoparticle was synthesized by using precipitation method and characterized via UV test & XRD test for particle grain size. It was then blended with a conventional lubricant with 0.03% concentration by weight. The nanoparticle blended lubricant was also characterized for thermophysical properties like density, kinematic viscosity, flash point and pour point. An experimental setup was established, featuring a standard 3.0 L four-stroke turbocharged diesel engine retrofitted with dip probe sensor to measure oil temperature of engine oil sump and a diagnostic software to measure coolant temperature commonly known as engine temperature. Engine tests were conducted under idle running condition for an hour, and the heat transfer rate of both conventional and nanoparticle blended lubricant was determined by analyzing the oil temperature and engine temperature data’s. The study observed a 3 °C increase in engine oil temperature from 49 °C with conventional lubricant to 52 °C with CuO-based nano lubricant, indicating enhanced thermal conductivity and improved heat dissipation properties of the nano-lubricant, highlighting the role of nanoparticle additives in reducing engine temperature and potentially enhancing engine life and performance.